(3GdeOGeI GdCQLhGfjI aj GdebGeI GdQVhGfjIs - (3eUWaj CSYO Hf CMeO Hf eMeO GHf SdGeI Gddbjej GdTGaYqj,J (B1178 (3g` s
(3ChdgG (B:s
(3hHYO, abO Mci GdHOjY HTjQ CHf SYO, bGd(B: (3MOKfj GdQHjY eLjQ Hf QTjO s
(3BNQgG (B:s
(3oNdbJ ceG CQGOJc GdeYGdj hcfJ def QLGc ceG jQjO hdeG Cfgi Gdbde HYV NOeJg hHqjV HeOGOg hLg UMjaJg, hba aj ebGe GdCOH hGdNVhY hGdGYJQGa s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B230 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B451s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B50 s
Keywords: (3GdCOHs